Socrates and the socratic dialogue - Stavru, Alessandro, 1971-; Moore, Christopher, 1981- (Classical Studies E-Books Online, Collection 2017, ISBN: 9789004327986., 2018)
Socrates and the Socratic Dialogue assembles the most complete range of studies on Socrates and the Socratic dialogue. It focuses on portrayals of Socrates, whether as historical figure or protagonist of 'Socratic dialogues', in extant and fragmentary texts from Classical Athens through Late Antiquity. Special attention is paid to the evolving power and texture of the Socratic icon as it adopted old and new uses in philosophy, biography, oratory, and literature. Chapters in this volume focus on Old Comedy, Sophistry, the first-generation Socratics including Plato and Xenophon, Aristotle and Aristoxenus, Epicurus and Stoicism, Cicero and Persius, Plutarch, Apuleius and Maximus, Diogenes Laertius, Libanius, Themistius, Julian, and Proclus.